2000
DOI: 10.1038/sj.leu.2401722
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute promyelocytic leukemia appears constant over most of a human lifespan, implying only one rate limiting mutation

Abstract: It is believed that most malignancies become more common with increasing age due to the requirement for several mutations to accumulate and subsequently interact. The age specific incidence of acute promyelocytic leukemia (APL) was investigated using population-based data from 77 million subject years of observation, yielding 149 consecutive cases. The incidence appears approximately constant with respect to age, an observation not previously reported with any other malignancy. These findings are most easily e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 33 publications
2
50
1
Order By: Relevance
“…A recent study which showed that the incidence rate of acute promyelocytic leukaemia (which is synonymous with t(15;17)) is constant with age supports these findings (Vickers et al, 2000). It is generally assumed that cancer incidence increases with age because of the time required to accumulate the requisite number of mutations to effect malignant transformation.…”
Section: Discussionmentioning
confidence: 85%
“…A recent study which showed that the incidence rate of acute promyelocytic leukaemia (which is synonymous with t(15;17)) is constant with age supports these findings (Vickers et al, 2000). It is generally assumed that cancer incidence increases with age because of the time required to accumulate the requisite number of mutations to effect malignant transformation.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, in PLZF-RARα transgenic mice, loss of wild-type Plzf was sufficient to modify a CML-like disease into APL (12), in lieu of the coexpression of RARα-PLZF. The extensive network of protein-protein interaction entertained by both fusion proteins and the functional contribution of these fusion proteins to cell transformation could explain the fact that the incidence of APL does not increase with age, consistent with one or a limited number of rate-limiting mutation(s) (1,35). Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Coimmunoprecipitations were performed using either in vitro translated 35 S radiolabeled protein, nuclear extracts, or cellular extracts from formaldehyde fixed cells as previously described (38). Individually synthesized proteins were preincubated for 30 min at 37°C to allow for protein-protein interactions to occur.…”
mentioning
confidence: 99%
“…9 Favourable cytogenetic abnormalities, t(15;17), t(8;21) and inv(16) are known to occur more frequently in younger patients, 9,14,15 with a relatively constant incidence throughout life. 15,16 For each of these balanced translocation groups, a much larger proportion of patients are in the younger age decades, giving a more even age-related incidence, in contrast to the greater weighting towards the oldest age decades seen in trisomic and deletional abnormalities. Furthermore, t(15;17), t(9;11) and inv(16) represent a significantly younger subset in our dataset.…”
Section: Discussionmentioning
confidence: 99%